Information Repackaging Strategy and Information Classification on the Instagram Account @perpustakaan_umy - Khaira Nadhlif Aulia; Alfia Nur Fadhila; Nita Siti Mudawamah (BACA: Jurnal Dokumentasi dan Informasi, 2026)
The purpose of this research is to explore how the @perpustakaan_umy Instagram account is managed to support the dissemination of information from the university library information. The method adopts a descriptive qualitative approach, with the study drawing on observation, documentation, and in-depth interviews with the social media team at the University of Muhammadiyah Yogyakarta Library, with the secondary data. Data analysis using by Miles and Huberman model. Findings show the library’s information repackaging strategy is both systematic and collaborative, made possible by creation of dedicated all from the social media division, clear task assignments, and the development of structure content plans. The efforts from the team’s supported by a content planner and coordinated teamwork. In managing Instagram content, information is thoughtfully organized from three main pillars: education, entertainment, and information, which is this together help to make a balanced the content from these three pillars. The conclusion of this study is that the activities of classifying and repackaging information on @perpustakaan_umy can foster interaction with users. Therefore, the UMY Library can promote its services and knowledge. This can serve as a reference for other library institutions in developing their own social media platforms.